Human-Nature Connections: The Chhath Sun Festival as a Lens for Ontological Perspectives in Hinduism - Kumar, Payal (Journal of management, spirituality & religion, 2025)
This paper describes how the panentheistic Hindu philosophy of Vedanta helps us grasp the deep interrelationship between humans and nature, in contrast to the Judeo-Christian weltanschauung that holds sway today. A deeper understanding of these interactions may hold key insights to strengthen community bonding, as well as to global topics of concern such as sustainability and the unethical treatment of the natural world ‐ with Chhath Puja as the anchor and point of departure for popular expressions of religion and spirituality in India.